2016
DOI: 10.1038/ng.3520
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic analysis of malignant pleural mesothelioma identifies recurrent mutations, gene fusions and splicing alterations

Abstract: We analyzed transcriptomes (n = 211), whole exomes (n = 99) and targeted exomes (n = 103) from 216 malignant pleural mesothelioma (MPM) tumors. Using RNA-seq data, we identified four distinct molecular subtypes: sarcomatoid, epithelioid, biphasic-epithelioid (biphasic-E) and biphasic-sarcomatoid (biphasic-S). Through exome analysis, we found BAP1, NF2, TP53, SETD2, DDX3X, ULK2, RYR2, CFAP45, SETDB1 and DDX51 to be significantly mutated (q-score ≥ 0.8) in MPMs. We identified recurrent mutations in several genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

102
1,134
14
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 758 publications
(1,263 citation statements)
references
References 95 publications
102
1,134
14
13
Order By: Relevance
“…A comprehensive genomic analysis identified mutations in BAP1 in 23% of MPM samples (117). Similarly, somatic mutations in BAP1 have been reported in approximately 20% of cases of MPM (118) and linkage analysis demonstrated that germ-line mutations in BAP1 are associated with familial MPM (16).…”
Section: Targeting Epigenetic Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive genomic analysis identified mutations in BAP1 in 23% of MPM samples (117). Similarly, somatic mutations in BAP1 have been reported in approximately 20% of cases of MPM (118) and linkage analysis demonstrated that germ-line mutations in BAP1 are associated with familial MPM (16).…”
Section: Targeting Epigenetic Regulatorsmentioning
confidence: 99%
“…Somatic mutations leading to loss of NF2 have been described in numerous cancers, including MPM. The recently published comprehensive genomic profiling of MPM identified mutations in NF-2 in 19% of cases (117).…”
Section: Focal Adhesion Kinase (Fak) Inhibitorsmentioning
confidence: 99%
“…Those of pathogenic significance have been described in association with BAP1-TPDS malignancies [4,21,[24][25][26][27][28]. On the other hand, somatic mutations of BAP1 are a frequent event in MM [26,28,29], with a variable rate of occurrence depending on the molecular assay used. Somatic mutations described to date are both nucleotide-level and chromosomal mutations [30].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data support evaluation of DNA demethylating agents in combination with immune checkpoint inhibitors in MPM. Despite evidence that 5-AZA augmented responses to anti-CTLA therapy in preclinical models, a better translational strategy might be to combine DNA demethylating agents with pembrolizumab given recent observations that this PD-L1 inhibitor mediated a 17% objective response rate in MPM patients (134), and high levels of PD-L1 expression in MPM-particularly sarcomatoid subtypes (3). Observations that combined decitabine/GSK126 or 5-AZA/entinostat treatment markedly augment efficacy of adoptively transferred CTL or anti-PD-L1 via up-regulation of Th1 signaling and inhibition of immunosuppressive myeloid derived suppressor cells within the tumor microenvironment in murine cancer models (113,135) support evaluation of such combinatorial regimens in clinical settings.…”
Section: Epigenetic Strategies For Mesothelioma Therapymentioning
confidence: 99%
“…Recent advances in "omics" technologies have enabled comprehensive gene and transcriptome analyses that have provided considerable insight regarding the pathogenesis, prognosis, and treatment of MPM (2,3). Presently, less information is available regarding mechanisms and clinical relevance of epigenetic derangements in MPM (4,5).…”
Section: Introductionmentioning
confidence: 99%